Antioxidant and Acetylcholinesterase Inhibitor Potentials of the Stem Extract of Pternandra galeata - Suciati, Suciati; Inayah, Dwiki Nur; Widyawaruyanti, Aty; Rudiyansyah, Rudiyansyah (Vitae, 2022)
Background: Pternandra galeata belongs to the family Melastomataceae. It is a native flowering plant in Borneo Island that serve as food for monkey habitat. There has been limited study on the medicinal and chemical properties of this plant. Objectives: We investigated the acetylcholinesterase inhibitory activity and evaluated the antioxidant activity of the ethanolic extract of Pternandra galeata stem. The total phenolic content in the sample was also determined. Methods: The acetylcholinesterase inhibitory assays were performed using Ellman’s method. Two different methods were used to evaluate the antioxidant activity of 2,2-diphenyl-1-picryl hydrazyl (DPPH) and 2,2′-azinobis-(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) assays. The total phenolic content was determined by the Folin-Ciocalteu method by employing gallic acid as a reference. Results: The ethanolic extract of the P. galeata stems inhibited the AChE enzyme with an IC50value of 74.62 ± 0.89 µg/mL. The sample exhibited antioxidant activity in the DPPH assay with an IC50 value of 20.21 ± 0.08 µg/mL and 7.68 ± 0.09µg/mL in the ABTS scavenging assay. The total phenolic content was 164.71 ± 3.33 mg GAE/g extract. Conclusion: The ethanolic extract of the P. galeata stem can be a promising cholinesterase inhibitor and antioxidant for treating Alzheimer’s disease.